Development of Interactive Learning Media Based on Canva on Human Respiratory System Material for Grade V at SD Negeri Galengdowo 1 - Winarni; Adi Bandono; Agung Pramuji (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
Learning about the human respiratory system at SD Negeri Galengdowo 1 faces obstacles due to the abstract nature of the material and the use of less interactive conventional media, resulting in more than 60% of students failing to reach the KKTP (75) with low conceptual understanding. This research aims to develop interactive learning media based on Canva on human respiratory system material that is valid, practical, and effective for fifth-grade students. The research method used is Research and Development (R&D) with the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were 28 fifth-grade students at SD Negeri Galengdowo 1. Data collection techniques used validation questionnaires, response questionnaires, and learning outcomes tests. The results show that the media is highly feasible with an average validation of 87.5% obtained from material expert validation of 89% and media expert validation of 86%. Practicality testing shows highly practical results with an average percentage of 95.95% obtained from teacher responses of 97.1% and student responses of 94.8%. Effectiveness testing shows very effective results with student learning completeness increasing from 14.3% to 100%, and N-Gain test results show an average of 0.554 (medium category) indicating increased understanding of the material. This interactive learning media successfully improves student learning outcomes and can be an effective solution in teaching abstract science concepts in elementary schools.